La influencia de los textos narrativos en el desarrollo de los procesos orales en los niños del grado transición Aº del Colegio la Salle de Bello (2018)
The main idea of this paper is to study the influence that narrative texts have on the development of oral processes in children from 5 to 6 years that attend the “transition A” grade in La Salle de Bello School. The principal objective of the project is to analyze the influence that narrative texts have on the development of oral processes in children of “transition A”. The project also has the purpose of acquiring results that allow achieving significant conclusions, guided by the data obtained throughout the research process. This is a qualitative study with a hermeneutical approach. It is based on different techniques such as drawing, playing, semi-structured interview and participant observation. All those previus techniques are used in order to collect relevant information to analyze and thus achieve the objectives proposed. This work allows to understanding of the development that takes place in the construction of oral processes and the formation of integral processes in the meaningful learning. That could be observed in the execution of the plans proposed by the researching teachers, which concluded that the narrative text is a learning tool that favors the oral processes of the students in an initial stage, allowing to strengthen their communicative, social and cognitive skills that later would facilitate in the future the learning of more complex processes such as reading and writing